2011
DOI: 10.3892/or.2010.1077
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PAR2 or/and TLR4 promotes SW620 cell proliferation and migration via phosphorylation of ERK1/2

Abstract: Abstract. Protease-activated receptor 2 (PAR2) is a G-proteincoupled receptor and its activation has been associated with the pathogenetic progress in certain cancers. Toll-like receptor 4 (TLR4), one member of Toll-like receptors family, is mainly contributed to the innate immune response. However, recent studies have shown that TLR4 is aberrantly expressed in various types of carcinomas and may correlate with tumor progression. Previously, we reported that PAR2 could be expressed in human colon cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…When the cells were pre-incubated with EGCG (100 µg/mL), PAR2-AP-or factor VIIa-induced TF activity and MMP-9 expression were markedly decreased (P<0.01 vs PAR2-AP or factor VIIa alone), as shown in the black column in Figures 4A and 4B. EGCG alone seemed to Effects of EGCG on activation of ERK1/2 and NF-κB in SW620 cells Previously, we found that PAR2-AP and factor VIIa stimulated the activation of ERK1/2 and NF-κB (p65/RelA) in SW620 cells within 30 min of treatment [14,15] . In this study, we further investigated whether EGCG could influence the effects of PAR2-AP and factor VIIa on the levels of p-ERK1/2 and NF-κB (p65/RelA) in the cells.…”
Section: Effects Of Egcg On the Expression Of Tf And Mmp-9 In Sw620 Cmentioning
confidence: 68%
See 1 more Smart Citation
“…When the cells were pre-incubated with EGCG (100 µg/mL), PAR2-AP-or factor VIIa-induced TF activity and MMP-9 expression were markedly decreased (P<0.01 vs PAR2-AP or factor VIIa alone), as shown in the black column in Figures 4A and 4B. EGCG alone seemed to Effects of EGCG on activation of ERK1/2 and NF-κB in SW620 cells Previously, we found that PAR2-AP and factor VIIa stimulated the activation of ERK1/2 and NF-κB (p65/RelA) in SW620 cells within 30 min of treatment [14,15] . In this study, we further investigated whether EGCG could influence the effects of PAR2-AP and factor VIIa on the levels of p-ERK1/2 and NF-κB (p65/RelA) in the cells.…”
Section: Effects Of Egcg On the Expression Of Tf And Mmp-9 In Sw620 Cmentioning
confidence: 68%
“…Factor VIIa can activate PAR2 and promote SW620 cell proliferation and migration in a TF-dependent manner. Some intracellular signaling molecules, such as ERK1/2 and NF-κB, are activated in these processes [9,14,15] . The anti-tumor properties of EGCG have received much attention in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Tremendous undesired effects, and in particular severe metabolic toxicity similar to diabetes mellitus complications, were expected from these molecules that tend to inhibit all ILP activity. Instead, evidence from early clinical experience indicates that these agents are safe and, therefore, promising, given their broader range of receptor inhibition , Zhou et al 2011. The mechanisms explaining the absence of the expected side effects still are to be unraveled, even though some plausible explanations have been suggested.…”
Section: Insulin Resistance Infection and Cancermentioning
confidence: 99%
“…This promoted VEGF expression and resistance to apoptosis. Similarly, in SW620 cells (colon cancer cell line), TLR4 promoted cell proliferation and migration through phosphorylation of ERK 1/2 (Zhou et al 2011). Downregulation of TLR4 with siRNA inhibited prostate cancer cell invasion and survival (Hua et al 2009).…”
Section: Discussionmentioning
confidence: 99%